Ceramic coating as well as preparation method, application and use method thereof
By using functional fillers such as high-entropy zirconate, hexagonal boron nitride and silicon nitride in the coating, and combined with composite adhesive design, ceramic coatings are formed, which solves the problem of poor corrosion resistance of existing coatings at high temperatures, and achieves high adhesion and stain resistance of the coating, which significantly improves the protection effect of the boiler heating surface.
Patent Information
- Application Number
- CN202510668462.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-06-24
- Estimated Expiration
- 2045-05-23
AI Technical Summary
The existing coatings have poor corrosion resistance at high temperatures, and traditional thermal spraying technology has problems such as dust pollution, low material utilization rate and long construction period, making it difficult to effectively prevent contamination and slag on the boiler's heated surface.
Functional fillers such as high entropy zirconate, hexagonal boron nitride, silicon nitride and other functional fillers are used to combine the composite design of inorganic and organic binders to form ceramic coatings. The coating is formed by spraying the first curing and the second curing to form a protective layer, which improves the adhesion of the coating and anti-staining properties.
The coating formed by ceramic coatings has excellent high temperature resistance, adhesion and stain slag resistance, which can effectively prevent stain slag on the heated surface of the boiler, reduce the risk of corrosion, and improve the durability and economicality of the coating.
Smart Images

Figure CN120192687A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a ceramic coating, a preparation method and an application thereof, and a using method. Background Art
[0002] For a long time, fouling and slagging have been a major threat to the safe operation of power station boilers. Currently, with the widespread use of low-cost high-sulfur coal and high-reserve high-sodium coal (such as Zhundong coal), the fouling and slagging problems faced by the heating surfaces of power station boilers, such as water walls, superheaters and reheaters, are becoming increasingly serious. At the same time, problems such as insufficient heat absorption of the water wall, too high flue gas temperature at the furnace outlet and too high tube wall temperature are derived, significantly affecting the safety and economy of power plant operation.
[0003] In order to alleviate this fouling, slagging and accompanying corrosion problems, scholars at home and abroad have carried out a large number of studies and proposed effective protection methods, mainly focusing on the following four aspects: (1) Coal pretreatment: The coal is upgraded to reduce the content of sulfur, chlorine and alkali metal elements, which inhibits the generation of corrosive deposits to a certain extent and reduces the adhesion on the heating surface; (2) Coal modification: Adding kaolin, corundum, etc. to the coal to change its silicon-aluminum ratio, playing a role in fixing volatile alkali metal elements, and at the same time increasing its melting point to alleviate the fouling and slagging degree; (3) Boiler structure design and modification: including boiler furnace type and size design, combustion equipment optimization design, flue gas recirculation design, horizontal thick-thin air combustion technology and wall-attached air technology, etc., optimizing the combustion process, promoting the oxidation of deposits in the flame, and inhibiting the generation of reducing atmosphere on the surface of the heating surface, thereby effectively reducing the risk of fouling and slagging; (4) Coating protection: Using thermal spraying methods such as arc spraying, plasma spraying and supersonic flame spraying to atomize powders or filaments of metals into molten droplets, which hit the surface of the heating surface at high speed to form a corrosion-resistant protective layer with a certain thickness, effectively protecting the boiler matrix from damage.
[0004] Considering the difficulty of large-scale modified coal and the high cost of large-scale boiler structure modification, using coating protection technology to improve the fouling and slagging problems of boiler heating surfaces has become the current mainstream method. However, traditional thermal spraying technologies have disadvantages such as poor working environment, serious dust pollution, low material utilization rate and long construction period, and there is an urgent need to develop a new protection method.
[0005] Among existing protective coatings, one type is organic high-temperature resistant coatings, which mainly use silicone resin as a binder and add functional fillers and additives in a certain proportion. However, the temperature resistance of such coatings is limited, and the long-term maximum service temperature is generally in the range of 400 - 500 °C. Moreover, the molecular chains of organic resins are prone to breakage and cracking at high temperatures, resulting in a significant decline in the anti-corrosion performance of the coatings.
[0006] Another type is inorganic high-temperature resistant coatings, which mainly use sodium silicate water glass or inorganic silicone resin as film-forming substances and are formulated with a variety of high-temperature resistant fillers. Such coatings usually have good high-temperature performance, but poor salt spray corrosion resistance. In addition, due to the large difference in thermal expansion coefficients between the inorganic film-forming substances and the carbon steel substrate, the coatings are prone to stress concentration during the alternating use of hot and cold, resulting in cracking and even peeling failure.
[0007] Therefore, it is of great engineering application value to develop an anti-fouling and slagging coating that can meet the requirements of high-temperature use and has excellent adhesion. Summary of the Invention
[0008] In view of this, the purpose of the present invention is to provide a ceramic coating, its preparation method, application, and usage method. The ceramic coating formed by the ceramic coating provided by the present invention can meet the requirements of high-temperature use and has excellent adhesion and anti-fouling and slagging properties.
[0009] To achieve the above-mentioned invention purpose, the present invention provides the following technical solutions: The present invention provides a ceramic coating, which includes the following components by mass percentage: High-entropy zirconate 20 - 34%, Al2O3 whiskers 1 - 2%, hexagonal boron nitride 1 - 3%, silicon nitride 1 - 3%, cordierite 2 - 4%, chromium oxide 6 - 8%, wetting dispersant 0.3 - 1%, leveling agent 0.3 - 1%, defoaming agent 0.3 - 1%, thickening agent 0.3 - 1%, composite binder 35 - 50%, water 10 - 20%; The chemical formula of the high-entropy zirconate is A2Zr2O7, where the A site contains at least four elements among La, Sm, Nd, Gd, Eu, Yb, Y, and Sc, and the elements in the A site are in equimolar ratio; The composite binder includes an organic binder and an inorganic binder.
[0010] Preferably, the particle size of the high-entropy zirconate < 1 μm, and the specific surface area is 30 - 80 m 2 / g; The particle size of the hexagonal boron nitride is 200 - 300 nm; The particle size of the silicon nitride is 600 - 800 nm; The particle size of the cordierite < 1 μm; The particle size of the chromium oxide is < 1 μm.
[0011] Preferably, the wetting dispersant is an anionic wetting dispersant; The leveling agent is a silicone leveling agent; The defoaming agent is one or more of silicone defoaming agents, polyether silicone defoaming agents, and mineral oil-based defoaming agents; The thickening agent is a polyurethane thickening agent and / or a non-ionic thickening agent.
[0012] Preferably, the organic binder includes one or more of styrene-acrylic emulsion, silicone-acrylic emulsion, and pure acrylic emulsion; in the ceramic coating, the mass percentage content of the organic binder is 15-25%; The inorganic binder includes one or more of potassium silicate water glass, sodium silicate water glass, and lithium silicate water glass; in the ceramic coating, the mass percentage content of the inorganic binder is 20-35%.
[0013] The present invention provides a preparation method of the ceramic coating described in the above technical solution, including the following steps: Mix the wetting dispersant, leveling agent, defoaming agent, thickening agent, and water for the first time to obtain a first system; Mix the high-entropy zirconate, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, chromium oxide, and composite binder for the second time to obtain a second system; After the first system and the second system are mixed for the third time, grinding is carried out to obtain the ceramic coating.
[0014] Preferably, the rotation speed of the first mixing is 2000-2500 r / min, and the time is 5-15 min; The rotation speed of the second mixing is 600-800 r / min, and the time is 10-20 min; The rotation speed of the third mixing is 200-300 r / min, and the time is 30-40 min; The grinding balls for the grinding are zirconia grinding balls, the rotation speed of the grinding is 300-500 rpm, and the time is 2-3 h.
[0015] The present invention also provides an application of the ceramic coating described in the above technical solution in the field of protection.
[0016] The present invention also provides a usage method of the ceramic coating described in the above technical solution, including the following steps: Perform sandblasting treatment on the substrate to be protected to obtain a treated substrate; Spray the ceramic coating described in the above technical solution on the treated substrate, and perform first curing and second curing in sequence to form a protective layer.
[0017] Preferably, the parameters of the sandblasting treatment include: the particle size of the corundum sand is 24 - 150 mesh, and the pressure is 0.5 - 2 MPa; The pressure of the spraying is 0.4 - 1.5 MPa, the ambient temperature is 15 - 25 °C, and the relative air humidity is 40 - 60%.
[0018] Preferably, the time of the first curing is 12 - 24 h; The temperature of the second curing is 200 - 600 °C, and the time is 2 - 6 h.
[0019] The present invention provides a ceramic coating.
[0020] The beneficial effects of the present invention are as follows: 1. The present invention selects high-entropy zirconate as the main functional filler, and obtains a single-phase solid solution with a pyrochlore structure through a high-entropy design of equimolar doping of multiple components at the A site of the A2Zr2O7 zirconate. There are significant differences in ionic radius and mass between different doping elements, resulting in severe lattice distortion. Utilizing the high-entropy effect, lattice distortion effect, sluggish diffusion effect and "cocktail" effect of high-entropy zirconate, the ceramic coating has excellent thermal expansion coefficient, thermal conductivity and emissivity, improving the high-temperature resistance and adhesion of the ceramic coating.
[0021] 2. The present invention uses low-surface-energy materials hexagonal boron nitride and silicon nitride as part of the functional fillers, which is crucial for improving the anti-fouling and slagging performance of the ceramic coating. Both hexagonal boron nitride and silicon nitride are at the nanoscale and can be evenly distributed inside the coating during the spraying process. They are interconnected to form a low-surface-energy layer during the second curing process of the ceramic coating, effectively inhibiting the adhesion of coal combustion products on the surface.
[0022] 3. The present invention combines an inorganic binder and an organic binder, making the ceramic coating have excellent high-temperature resistance and extremely high toughness; at the same time, adding Al2O3 whiskers and compounding with the composite binder, absorbing energy through the weak interface between the composite binder and the coating matrix after the second curing, and causing the cracks to deflect and branch during the propagation process, effectively realizing the toughening of the coating.
[0023] 4. The ceramic coating formed by the ceramic coating provided by the present invention has excellent thermal shock resistance. The steel materials of the water-cooled wall tubes of power station boilers include 20G, 20MnG, 15MoG, 15CrMoG, 12Cr1MoVG, etc., and the thermal expansion coefficients are distributed in the range of 9 - 13×10 -6 K -1 According to the test standard of GB / T 7320-2018 "Thermal Expansion Coefficient of Coatings", the thermal expansion coefficient of the coating formed by the ceramic coating of the present invention is 9.5 - 11.8×10 -6 K -1, which is matched with the substrate, can effectively reduce the thermal stress caused by the mismatch of the thermal expansion coefficients of the coating and the substrate during the cyclic heating and cooling process, and improve the adhesion of the ceramic coating.
[0024] 5. The ceramic coating formed by the ceramic coating provided by the present invention has excellent anti-SO2 gas corrosion performance. Description of the Drawings
[0025] Figure 1 It is a schematic diagram of the device for measuring the slag wettability on the surface of the ceramic coating formed by the ceramic coating provided by the present invention; Figure 2 It is a physical picture of the ceramic coating formed by the ceramic coating obtained in Example 1 before and after the thermal shock test; Figure 3 It is a physical picture of the ceramic coating formed by the ceramic coating obtained in Example 1 before and after the SO2 gas corrosion. Detailed Embodiments
[0026] The present invention provides a ceramic coating, which comprises the following components by mass percentage: 20-34% of high-entropy zirconate, 1-2% of Al2O3 whiskers, 1-3% of hexagonal boron nitride, 1-3% of silicon nitride, 2-4% of cordierite, 6-8% of chromium oxide, 0.3-1% of wetting and dispersing agent, 0.3-1% of leveling agent, 0.3-1% of defoaming agent, 0.3-1% of thickening agent, 35-50% of composite binder, and 10-20% of water; The chemical formula of the high-entropy zirconate is A2Zr2O7, wherein the A site contains at least four elements among La, Sm, Nd, Gd, Eu, Yb, Y, and Sc, and the elements in the A site are in equimolar ratio; The composite binder includes an organic binder and an inorganic binder.
[0027] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0028] In terms of mass percentage, the ceramic coating provided by the present invention comprises 20 - 34% of high-entropy zirconate, specifically preferably 20%, 21%, 22%, 23%, 24%, 25%, 26%, 26.33%, 27%, 28%, 28.34%, 29%, 29.55%, 30%, 30.23%, 31%, 32%, 33% or 34%. In the present invention, the chemical formula of the high-entropy zirconate is A2Zr2O7, where the A site contains at least four elements among La, Sm, Nd, Gd, Eu, Yb, Y, Sc, further preferably the combination of La, Nd, Sm, Eu and Gd, the combination of Yb, Nd, Sm, Eu and Gd, the combination of Gd, Yb, Y and Sc, or the combination of La, Nd, Yb and Y; the elements in the A site are in equimolar ratio. In the present invention, the preparation method of the high-entropy zirconate preferably comprises the following steps: mixing at least four of La2O3, Sm2O3, Nd2O3, Gd2O3, Eu2O3, Yb2O3, Y2O3, Sc2O3 and ZrO2, and successively performing calcination and ball milling to obtain the high-entropy zirconate. In the present invention, the ratio of the total molar amount of at least four of La2O3, Sm2O3, Nd2O3, Gd2O3, Eu2O3, Yb2O3, Y2O3, Sc2O3 to the molar amount of ZrO2 is preferably 1:2. In the present invention, the mixing is preferably carried out in a powder mixer, and the mixing time is preferably 2 h. In the present invention, the calcination temperature is preferably 1450 - 1600 °C, specifically preferably 1450 °C, 1500 °C, 1510 °C, 1520 °C, 1530 °C, 1540 °C, 1550 °C, 1560 °C, 1570 °C, 1580 °C, 1590 °C or 1600 °C; the heat preservation time is preferably 10 - 16 h, specifically preferably 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or 16 h. In the present invention, the rotation speed of the ball milling is preferably 200 - 500 rpm, specifically preferably 200 rpm, 300 rpm, 400 rpm or 500 rpm, and the time is preferably 1 - 2 h, specifically preferably 1 h, 1.5 h or 2 h; the ball milling is preferably carried out in a planetary ball mill, and the grinding balls for the ball milling are preferably zirconia grinding balls. In the present invention, the particle size of the high-entropy zirconate is preferably <1 μm, and the specific surface area is preferably 30 - 80 m 2 / g, specifically preferably 30 m 2 / g, 40 m 2 / g, 50 m 2 / g, 60 m 2 / g, 70 m 2 / g or 80 m 2 / g. In the present invention, a high-entropy design of equimolar doping of multiple components is carried out at the A-site of the high-entropy zirconate A2Zr2O7 to obtain a single-phase solid solution with a pyrochlore structure. There are significant differences in ionic radius and mass among different doping elements (including at least four elements among La, Sm, Nd, Gd, Eu, Yb, Y, and Sc), resulting in severe lattice distortion. By utilizing the high-entropy effect, lattice distortion effect, sluggish diffusion effect, and "cocktail" effect of the high-entropy zirconate, the ceramic coating has excellent thermal expansion coefficient, thermal conductivity, and emissivity, improving the high-temperature resistance and adhesion of the ceramic coating.
[0029] By mass percentage, the ceramic coating provided by the present invention includes 1-2% of Al2O3 whiskers, specifically preferably 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%.
[0030] By mass percentage, the ceramic coating provided by the present invention includes 1-3% of hexagonal boron nitride, specifically preferably 1%, 1.5%, 2%, 2.5%, or 3%. In the present invention, the particle size of the hexagonal boron nitride is preferably 200-300 nm, specifically preferably 200 nm or 300 nm.
[0031] By mass percentage, the ceramic coating provided by the present invention includes 1-3% of silicon nitride, specifically preferably 1%, 1.5%, 2%, 2.5%, or 3%. In the present invention, the particle size of the silicon nitride is preferably 600-800 nm, specifically preferably 600 nm, 700 nm, or 800 nm. In the present invention, using low-surface-energy materials hexagonal boron nitride and silicon nitride as part of the functional fillers is crucial for improving the anti-fouling and slagging performance of the ceramic coating. Both hexagonal boron nitride and silicon nitride are at the nanoscale and can be evenly distributed inside the coating during the spraying process, and connect with each other to form a low-surface-energy layer during the secondary curing of the ceramic coating, effectively inhibiting the adhesion of coal combustion products on the surface.
[0032] By mass percentage, the ceramic coating provided by the present invention includes 2-4% of cordierite, specifically preferably 2%, 2.5%, 3%, 3.2%, 3.5%, or 4%. In the present invention, the particle size of the cordierite is preferably <1 μm, further preferably 500-800 nm, specifically preferably 500 nm, 600 nm, 700 nm, or 800 nm.
[0033] By mass percentage, the ceramic coating provided by the present invention includes 6-8% of chromium oxide, specifically preferably 6%, 6.5%, 7%, 7.5%, or 8%. In the present invention, the particle size of the chromium oxide is preferably <1 μm, further preferably 500-900 nm, specifically preferably 500 nm, 600 nm, 700 nm, 800 nm, or 900 nm.
[0034] In terms of mass percentage, the ceramic coating provided by the present invention comprises 0.3 - 1% of a wetting dispersant, specifically preferably 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In the present invention, the wetting dispersant is preferably an anionic wetting dispersant, and the anionic wetting dispersant is preferably one or more of Disperbyk TEGO-750W weak anionic polymer wetting dispersant, Disperbyk TEGO-757W anionic polymer wetting dispersant and Disperbyk TEGO-715W anionic wetting dispersant.
[0035] In terms of mass percentage, the ceramic coating provided by the present invention comprises 0.3 - 1% of a leveling agent, specifically preferably 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In the present invention, the leveling agent is preferably a silicone leveling agent, and the silicone leveling agent is further preferably one or more of BYK-300 silicone leveling agent, BYK-333 silicone leveling agent and Disperbyk TEGO Glide 440 leveling agent.
[0036] In terms of mass percentage, the ceramic coating provided by the present invention comprises 0.3 - 1% of an antifoaming agent, specifically preferably 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In the present invention, the antifoaming agent is preferably one or more of silicone antifoaming agents, polyether silicone defoamers and mineral oil-based defoamers. Specifically, the silicone antifoaming agent is preferably BYK-024 silicone antifoaming agent, the polyether silicone defoamer is preferably Disperbyk TEGO-901W polyether silicone defoamer, and the mineral oil-based defoamer is preferably King Industries Deform W-082 mineral oil-based defoamer.
[0037] In terms of mass percentage, the ceramic coating provided by the present invention comprises 0.3 - 1% of a thickening agent, specifically preferably 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In the present invention, the thickening agent is preferably a polyurethane thickening agent and / or a non-ionic thickening agent. Specifically, the polyurethane thickening agent is preferably Disperbyk TEGO ViscoPlus 3030 polyurethane thickening agent, and the non-ionic thickening agent is preferably Disperbyk TEGO ViscoPlus 3060 non-ionic thickening agent.
[0038] In terms of mass percentage, the ceramic coating provided by the present invention comprises 35 - 50% of a composite binder, more preferably 40 - 45%, and specifically preferably 35%, 36%, 37%, 38%, 39%, 40%, 41%, 41.45%, 43%, 45% or 50%. In the present invention, the organic binder preferably comprises one or more of styrene-acrylic emulsion, silicone-acrylic emulsion and pure acrylic emulsion. In the present invention, the solid content of the organic binder is preferably 40 - 60%, specifically preferably 40%, 45%, 50%, 55% or 60%. In a specific embodiment of the present invention, the styrene-acrylic emulsion is specifically preferably BASF Anchorite 7538, the silicone-acrylic emulsion is specifically preferably BF-400 silicone-acrylic emulsion, and the pure acrylic emulsion is specifically preferably BASF Anchorite 7051. In the present invention, in the ceramic coating, the mass percentage of the organic binder is 15 - 25%, specifically preferably 15%, 19.45%, 20% or 25%. In the present invention, the inorganic binder preferably comprises one or more of potassium silicate water glass, sodium silicate water glass and lithium silicate water glass; the modulus of the inorganic binder is preferably 2.6 - 3.8. In the present invention, in the ceramic coating, the mass percentage of the inorganic binder is preferably 20 - 35%, specifically preferably 20%, 22%, 25%, 26%, 28%, 30%, 32% or 35%. In the present invention, the inorganic binder and the organic binder are compounded to endow the ceramic coating with excellent high-temperature resistance and extremely high toughness; meanwhile, Al2O3 whiskers are added and compounded with the composite binder, and the energy is absorbed through the weak interface between the composite binder and the coating matrix after the second curing, and cracks are deflected and branched during the propagation process, effectively realizing the toughening of the coating.
[0039] In terms of mass percentage, the ceramic coating provided by the present invention comprises 10 - 20% of water, specifically preferably 10%, 10.26%, 11%, 11.17%, 11.6%, 12%, 13%, 13.37%, 14%, 15%, 16%, 17%, 18%, 19% or 20%. In the present invention, the water is preferably deionized water.
[0040] The present invention provides a preparation method of the ceramic coating according to the above technical solution, comprising the following steps: Mix a wetting dispersant, a leveling agent, an antifoaming agent, a thickening agent and water for the first time to obtain a first system; Mix high-entropy zirconate, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, chromium oxide and a composite binder for the second time to obtain a second system; After the first system and the second system are mixed for the third time, grinding is carried out to obtain the ceramic coating.
[0041] In the present invention, a wetting dispersant, a leveling agent, an antifoaming agent, a thickening agent and water are first mixed to obtain a first system. In the present invention, the rotation speed of the first mixing is preferably 2000 - 2500 r / min, specifically preferably 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min or 2500 r / min; the time is preferably 5 - 15 min, specifically preferably 5 min, 10 min or 15 min.
[0042] In the present invention, a high-entropy zirconate, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, chromium oxide and a composite binder are second mixed to obtain a second system. In the present invention, the rotation speed of the second mixing is preferably 600 - 800 r / min, specifically preferably 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min; the time is preferably 10 - 20 min, specifically preferably 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min.
[0043] After obtaining the first system and the second system, in the present invention, the first system and the second system are third mixed and then ground to obtain the ceramic coating. In the present invention, the rotation speed of the third mixing is preferably 200 - 300 r / min, specifically preferably 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min or 300 r / min; the time is preferably 30 - 40 min, specifically preferably 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min. In the present invention, the grinding balls for grinding are preferably zirconia grinding balls, the rotation speed of the grinding is preferably 300 - 500 rpm, specifically preferably 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm; the time is preferably 2 - 3 h, specifically preferably 2 h, 2.5 h or 3 h. In the present invention, the grinding is preferably carried out in a planetary ball mill. After the ball milling, the present invention preferably further includes filtration, and the aperture of the sieve for filtration is preferably 1000 - 2000 mesh, specifically preferably 1000 mesh or 2000 mesh.
[0044] The present invention also provides the application of the ceramic coating as described in the above technical solution in the field of protection.
[0045] In the present invention, the protection preferably includes aerospace protection or boiler protection. In the present invention, the boiler protection is further preferably the protection of the boiler water wall, and the material of the boiler water wall preferably includes steel 20G, steel 20MnG, steel 15MoG, steel 15CrMoG or steel 12Cr1MoVG.
[0046] The present invention also provides a method for using the ceramic coating described in the above technical solution, including the following steps: Perform sandblasting on the substrate to be protected to obtain a treated substrate; Spray the ceramic coating described in the above technical solution on the treated substrate, and successively perform first curing and second curing to form a protective layer.
[0047] In the present invention, sandblasting is performed on the substrate to be protected to obtain a treated substrate. In the present invention, the parameters of the sandblasting include: the particle size of the corundum sand is preferably 24 - 150 mesh, specifically preferably 24 mesh, 30 mesh, 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh or 150 mesh; the pressure is preferably 0.5 - 2 MPa, specifically preferably 0.5 MPa, 1 MPa, 1.5 MPa or 2 MPa. The present invention does not specifically limit the time of the sandblasting, as long as the surface cleanliness of the substrate to be protected can reach Sa2.5 level.
[0048] After obtaining the treated substrate, in the present invention, the ceramic coating described in the above technical solution is sprayed on the treated substrate, and successively perform first curing and second curing to form a protective layer.
[0049] In the present invention, the pressure of the spraying is preferably 0.4 - 1.5 MPa, specifically preferably 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa or 1.5 MPa; the ambient temperature is preferably 15 - 25 °C, specifically preferably 15 °C, 16 °C, 17 °C, 18 °C, 19 °C, 20 °C, 21 °C, 22 °C, 23 °C, 24 °C or 25 °C; the relative air humidity is preferably 40 - 60%, specifically preferably 40%, 45%, 50%, 55% or 60%. In the present invention, the thickness of the wet film obtained by the spraying is preferably 100 - 200 μm, specifically preferably 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0050] In the present invention, the temperature of the first curing is preferably room temperature, i.e., neither additional heating nor additional cooling is required. The time is preferably 12 to 24 hours, specifically preferably 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0051] In the present invention, the temperature of the second curing is preferably 200 to 600 °C, specifically preferably 200 °C, 300 °C, 400 °C, 500 °C or 600 °C; the heating rate for heating up to the temperature of the second curing is preferably 1 to 10 °C / min, specifically preferably 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min or 10 °C / min; the time is preferably 2 to 6 hours, specifically preferably 2 hours, 3 hours, 4 hours, 5 hours or 6 hours; the second curing is preferably carried out in a box furnace. After the second curing, the present invention preferably further includes cooling with the furnace.
[0052] The following examples are used to illustrate in detail the ceramic coating provided by the present invention, its preparation method, application and usage method, but they should not be construed as limiting the protection scope of the present invention.
[0053] Example 1 1. Raw material preparation A high-entropy zirconate ceramic coating (1000 g) resistant to high-temperature fouling and slagging is composed of the following components: La2O3 32.6 g (0.1 mol), Nd2O3 33.6 g (0.1 mol), Sm2O3 34.8 g (0.1 mol), Eu2O3 35.2 g (0.1 mol), Gd2O3 36.3 g (0.1 mol), ZrO2 123 g (1 mol), Al2O3 whiskers 12 g, hexagonal boron nitride (particle size of 300 nm) 20 g, silicon nitride (particle size of 800 nm) 20 g, cordierite (particle size of 800 nm) 32 g, chromium oxide (particle size of 800 nm) 70 g, wetting and dispersing agent (Degussa TEGO-750W) 3 g, leveling agent (BYK-300) 9 g, defoaming agent (BYK-024) 5 g, thickening agent (Degussa TEGOViscoPlus 3030) 3 g, sodium silicate water glass (modulus of 2.6 - 2.7) 220 g, silicon-acrylic emulsion (BF-400 silicon-acrylic emulsion) 194.5 g, deionized water 116 g.
[0054] 2. Coating preparation (1) The prepared wetting and dispersing agent, leveling agent, defoaming agent and thickening agent are successively added to deionized water and stirred evenly. The stirring speed is 2200 r / min and the stirring time is 10 min to obtain the first system.
[0055] (2) Mix the prepared La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, and ZrO2 in a powder mixer for 2 h, then calcine at a high temperature of 1550 °C for 14 h, and finally ball mill using zirconia grinding balls in a planetary ball mill at a ball milling speed of 300 rpm for 1 h to obtain high-entropy zirconate (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic powder with a particle size less than 1 μm and a specific surface area of 70 m 2 / g.
[0056] (3) Add the prepared (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 powder, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, and chromium oxide into the composite binder (sodium silicate water glass and silicon-acrylic emulsion) in sequence and stir evenly at a stirring speed of 600 r / min for 10 min to obtain the second system.
[0057] (4) Mix the first system and the second system and stir evenly at a stirring speed of 200 r / min for 30 min, then perform ball milling and dispersion using zirconia grinding balls in a planetary ball mill at a ball milling speed of 300 rpm for 2 h, and finally filter through a 2000-mesh sieve to obtain high-entropy zirconate (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic coating.
[0058] 3. Coating preparation (1) Pretreatment: Blast the 20G substrate with 150-mesh corundum sand at a pressure of 0.5 MPa to make the surface cleanliness reach Sa2.5 level.
[0059] (2) Spraying: Deposit the high-entropy zirconate (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic coating on the surface of the 20G substrate by air spraying method at a spraying pressure of 0.4 MPa, an environmental temperature of 18 °C, and a relative air humidity of 50% to obtain a wet film with a thickness of 130 μm ± 20 μm.
[0060] (3) High-temperature curing: The wet film sample was cured at room temperature for 24 h, then heated in a box furnace to 600 °C at a heating rate of 5 °C / min, with a high-temperature curing time of 2 h, and then cooled in the furnace to obtain a dry film high-entropy zirconate (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic coating.
[0061] 4. Performance testing (1) Cinder wettability: The cinder was ground into powder, then pressed into small cylinders with a diameter and height of 3 mm, placed on the surface of the coating sample, heated to 600 °C at a heating rate of 5 °C / min, and the morphological evolution of the cinder cylinders was recorded in real time using a high-speed camera, and the contact angle was measured. The schematic diagram is as Figure 1 shown.
[0062] (2) High-temperature stability: The coating sample was placed in a box furnace, heated to 800 °C at a heating rate of 10 °C / min, held for 720 h, and after removal, the phase structure of the coating was determined and the surface morphology of the coating was observed.
[0063] (3) Thermal shock resistance: The coating sample was placed in a box furnace, heated to 600 °C at a heating rate of 10 °C / min, held for 55 min, removed and air-cooled for 5 min as a cycle. After 70 cycles, the surface morphology of the coating was observed.
[0064] (4) Corrosion resistance: It was determined with reference to "GB / T 9789-2008 Metallic and other inorganic coatings - Corrosion test by sulfur dioxide in the presence of general condensation".
[0065] (5) Hardness: It was determined with reference to "GB / T 6739-2006 Paints and varnishes - Determination of film hardness by pencil test".
[0066] (6) Tensile strength: It was determined with reference to "GB / T 5210-2006 Paints and varnishes - Pull-off adhesion test".
[0067] (7) Infrared emissivity: It was determined with reference to "GB 4653-1984 General technical conditions for infrared radiation coatings".
[0068] The performance indexes of the coating are shown in Table 1.
[0069] Example 2 1. Raw material preparation A high-entropy zirconate ceramic coating (1000 g) resistant to high-temperature fouling and slagging, consisting of the following components: 39.4 g (0.1 mol) of Yb2O3, 33.6 g (0.1 mol) of Nd2O3, 34.8 g (0.1 mol) of Sm2O3, 35.2 g (0.1 mol) of Eu2O3, 36.3 g (0.1 mol) of Gd2O3, 123 g (1 mol) of ZrO2, 20 g of Al2O3 whiskers, 30 g of hexagonal boron nitride (particle size 200 nm), 30 g of silicon nitride (particle size 600 nm), 30 g of cordierite (particle size 800 nm), 80 g of chromium oxide (particle size 500 nm), 5 g of wetting and dispersing agent (Degussa TEGO-715W), 10 g of leveling agent (BYK-333), 3 g of defoaming agent (Degussa TEGO-901W), 6 g of thickening agent (Degussa TEGO ViscoPlus 3030), 200 g of potassium silicate water glass (modulus 3.0 - 3.1), 150 g of pure acrylic emulsion (BASF Acronal 7051), and 133.7 g of deionized water.
[0070] 2. Coating Preparation (1) Add the prepared wetting and dispersing agent, leveling agent, defoaming agent, and thickening agent to deionized water in sequence and stir evenly at a stirring speed of 2000 r / min for 10 min to obtain the first system.
[0071] (2) Mix the prepared Yb2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, and ZrO2 in a powder mixer for 2 h, then calcine at a high temperature of 1580 °C for 12 h, and finally ball-mill using zirconia grinding balls in a planetary ball mill at a ball-milling speed of 300 rpm for 1 h to obtain high-entropy zirconate (Yb 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic powder with a particle size less than 1 μm and a specific surface area of 50 m 2 / g.
[0072] (3) Add the prepared (Yb 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 powder, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, and chromium oxide to the composite binder (potassium silicate water glass and BASF Acronal 7051) in sequence and stir evenly at a stirring speed of 800 r / min for 15 min to obtain the second system.
[0073] (4) Mix the first system and the second system and stir evenly at a stirring speed of 200 r / min for 30 min. Then, use zirconia grinding balls in a planetary ball mill for ball milling and dispersion at a ball milling speed of 300 rpm for 2 h. Finally, filter through a 2000-mesh sieve to obtain the high-entropy zirconate (Yb 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic coating.
[0074] 3. Coating preparation (1) Pretreatment: Blast the 12Cr1MoVG substrate with 150-mesh corundum sand at a pressure of 0.5 MPa to achieve a surface cleanliness of Sa2.5 level.
[0075] (2) Spraying: Use the air spraying method to deposit the high-entropy zirconate (Yb 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic coating on the surface of the 12Cr1MoVG substrate. The spraying pressure is 0.4 MPa, the ambient temperature is 23 °C, and the relative air humidity is 60% to obtain a wet film with a thickness of 150 μm ± 20 μm.
[0076] (3) High-temperature curing: Cure the wet film sample at room temperature for 24 h, then heat it up to 600 °C in a box furnace at a heating rate of 5 °C / min, and the high-temperature curing time is 2 h. Then, cool it down with the furnace to obtain a dry film of high-entropy zirconate (Yb 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic coating.
[0077] 4. Performance testing The testing method of the coating refers to the content of "4. Performance testing" in Example 1, and the performance indexes are shown in Table 1.
[0078] Example 3 1. Raw material preparation A high-entropy zirconate ceramic coating (1000 g) resistant to high-temperature fouling and slagging consists of the following components: 45.4 g (0.125 mol) of Gd2O3, 49.3 g (0.125 mol) of Yb2O3, 28.3 g (0.125 mol) of Y2O3, 17.3 g (0.125 mol) of Sc2O3, 123 g (1 mol) of ZrO2, 20 g of Al2O3 whiskers, 15 g of hexagonal boron nitride (particle size 200 nm), 15 g of silicon nitride (particle size 700 nm), 40 g of cordierite (particle size 500 nm), 80 g of chromium oxide (particle size 900 nm), 5 g of wetting and dispersing agent (Degussa TEGO-757W), 5 g of leveling agent (Degussa TEGO Glide 440), 5 g of defoaming agent (Elementis Deform W-082), 10 g of thickening agent (Degussa TEGO ViscoPlus 3060), 280 g of potassium silicate water glass (modulus 3.0 - 3.1), 150 g of silicone-acrylic emulsion (BF-400 silicone-acrylic emulsion), and 111.7 g of deionized water.
[0079] 2. Coating Preparation (1) Add the prepared wetting and dispersing agent, leveling agent, defoaming agent, and thickening agent to deionized water in sequence and stir evenly. The stirring speed is 2500 r / min and the stirring time is 5 min to obtain the first system.
[0080] (2) Mix the prepared Gd2O3, Yb2O3, Y2O3, Sc2O3, and ZrO2 in a powder mixer for 2 h, then calcine at a high temperature of 1600 °C for 10 h, and finally ball mill using zirconia grinding balls in a planetary ball mill. The ball milling speed is 300 rpm and the ball milling time is 1 h to obtain high-entropy zirconate (Gd 0.25 Yb 0.25 Y 0.25 Sc 0.25 )2Zr2O7 ceramic powder with a particle size less than 1 μm and a specific surface area of 60 m 2 / g.
[0081] (3) Add the prepared (Gd 0.25 Yb 0.25 Y 0.25 Sc 0.25 )2Zr2O7 powder, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, and chromium oxide to the composite binder (potassium silicate water glass and BF-400 silicone-acrylic emulsion) in sequence and stir evenly. The stirring speed is 600 r / min and the stirring time is 10 min to obtain the second system.
[0082] (4) Mix the first system and the second system and stir evenly at a stirring speed of 200 r / min for 30 min. Then, use zirconia grinding balls in a planetary ball mill for ball milling and dispersion at a ball milling speed of 300 rpm for 2 h. Finally, filter through a 1000-mesh sieve to obtain a high-entropy zirconate (Gd 0.25 Yb 0.25 Y 0.25 Sc 0.25 )2Zr2O7 ceramic coating.
[0083] 3. Coating preparation (1) Pretreatment: Blast the 15CrMoG substrate with 150-mesh corundum sand at a pressure of 0.5 MPa to achieve a surface cleanliness of Sa2.5 level.
[0084] (2) Spraying: Deposit the high-entropy zirconate (Gd 0.25 Yb 0.25 Y 0.25 Sc 0.25 )2Zr2O7 ceramic coating on the surface of the 15CrMoG substrate by air spraying at a spraying pressure of 0.4 MPa, an ambient temperature of 20 °C, and a relative air humidity of 50% to obtain a wet film with a thickness of 180 μm ± 20 μm.
[0085] (3) High-temperature curing: Cure the wet film sample at room temperature for 24 h, then heat it up to 600 °C in a box furnace at a heating rate of 5 °C / min, with a high-temperature curing time of 2 h, and then cool it down with the furnace to obtain a dry film of high-entropy zirconate (Gd 0.25 Yb 0.25 Y 0.25 Sc 0.25 )2Zr2O7 ceramic coating.
[0086] 4. Performance testing The test method for the coating refers to the content of "4. Performance testing" in Example 1, and the performance indicators are shown in Table 1.
[0087] Example 4 1. Raw material preparation A high-entropy zirconate ceramic coating (1000 g) resistant to high-temperature fouling and slagging consists of the following components: 40.8 g (0.125 mol) of La2O3, 42 g (0.125 mol) of Nd2O3, 49.3 g (0.125 mol) of Yb2O3, 28.3 g (0.125 mol) of Y2O3, 123 g (1 mol) of ZrO2, 18 g of Al2O3 whiskers, 30 g of hexagonal boron nitride (particle size 300 nm), 30 g of silicon nitride (particle size 600 nm), 30 g of cordierite (particle size 600 nm), 70 g of chromium oxide (particle size 600 nm), 4 g of wetting and dispersing agent (Degussa TEGO-750W), 8 g of leveling agent (BYK-300), 6 g of defoaming agent (Degussa TEGO-901W), 8 g of thickening agent (Degussa TEGOViscoPlus 3060), 260 g of lithium silicate water glass (modulus 3.6 - 3.8), 150 g of styrene-acrylic emulsion (BASF Anchorite 7538), and 102.6 g of deionized water.
[0088] 2. Coating preparation (1) Add the prepared wetting and dispersing agent, leveling agent, defoaming agent, and thickening agent to deionized water in sequence and stir evenly at a stirring speed of 2500 r / min for 10 min to obtain the first system.
[0089] (2) Mix the prepared La2O3, Nd2O3, Yb2O3, Y2O3, and ZrO2 in a powder mixer for 2 h, then calcine at 1600 °C for 10 h, and finally ball mill in a planetary ball mill using zirconia grinding balls at a ball milling speed of 300 rpm for 1 h to obtain high-entropy zirconate (La 0.25 Nd 0.25 Yb 0.25 Y 0.25 )2Zr2O7 ceramic powder with a particle size less than 1 μm and a specific surface area of 60 m 2 / g.
[0090] (3) Add the prepared (La 0.25 Nd 0.25 Yb 0.25 Y 0.25 )2Zr2O7, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, and chromium oxide to the composite binder (lithium silicate water glass and BASF Anchorite 7538) in sequence and stir evenly at a stirring speed of 600 r / min for 20 min to obtain the second system.
[0091] (4) Mix the first system and the second system and stir evenly at a stirring speed of 200 r / min for 30 min. Then, use zirconia grinding balls in a planetary ball mill for ball milling and dispersion at a ball milling speed of 300 rpm for 2 h. Finally, filter through a 1000-mesh sieve to obtain the high-entropy zirconate (La 0.25 Nd 0.25 Yb 0.25 Y 0.25 )2Zr2O7 ceramic coating.
[0092] 3. Coating Preparation (1) Pretreatment: Blast the 20MnG substrate with 150-mesh corundum sand at a pressure of 0.5 MPa to achieve a surface cleanliness level of Sa2.5.
[0093] (2) Spraying: Deposit the high-entropy zirconate (La 0.25 Nd 0.25 Yb 0.25 Y 0.25 )2Zr2O7 ceramic coating on the surface of the 20MnG substrate by air spraying at a spraying pressure of 0.4 MPa, an ambient temperature of 25 °C, and a relative air humidity of 40% to obtain a wet film with a thickness of 150 μm ± 20 μm.
[0094] (3) High-temperature curing: Cure the wet film sample at room temperature for 24 h, then heat it up to 600 °C in a box furnace at a heating rate of 5 °C / min, and carry out high-temperature curing for 2 h. Then, cool it down with the furnace to obtain a dry film of high-entropy zirconate (La 0.25 Nd 0.25 Yb 0.25 Y 0.25 )2Zr2O7 ceramic coating.
[0095] 4. Performance Testing The testing method of the coating refers to the content of "4. Performance Testing" in Example 1, and the performance indexes are shown in Table 1.
[0096] Comparative Example 1 The difference from Example 1 is that the high-entropy zirconate (La 0.2 Nd 0.2 Sm 0.2 Eu 0.2 Gd 0.2 )2Zr2O7 ceramic powder is replaced with Gd2Zr2O7, and the others are the same as in Example 1.
[0097] Comparative Example 2 The difference from Example 1 is that hexagonal boron nitride is omitted and made up with water, and the others are the same as in Example 1.
[0098] Comparative Example 3 The difference from Example 1 is that silicon nitride is omitted and filled with water, and the others are the same as Example 1.
[0099] Comparative Example 4 The difference from Example 1 is that both hexagonal boron nitride and silicon nitride are omitted and filled with water, and the others are the same as Example 1.
[0100] Comparative Example 5 The difference from Example 1 is that Al2O3 whiskers are omitted and filled with water, and the others are the same as Example 1.
[0101] Comparative Example 6 The difference from Example 1 is that sodium silicate water glass is omitted and filled with silicon acrylic emulsion, and the others are the same as Example 1.
[0102] Comparative Example 7 The difference from Example 1 is that silicon acrylic emulsion is omitted and filled with sodium silicate water glass, and the others are the same as Example 1.
[0103] Table 1 Performance test results of the coatings in Examples and Comparative Examples
[0104] Figure 2 are the physical pictures of the ceramic coating formed by the ceramic coating obtained in Example 1 before and after the thermal shock test; from Figure 2 it can be seen that: after 70 thermal cycles of 600°C - room temperature for the obtained ceramic coating, there are no phenomena such as cracking, peeling, and blistering on the coating surface.
[0105] Figure 3 are the physical pictures of the ceramic coating formed by the ceramic coating obtained in Example 1 before and after the SO2 gas corrosion, from Figure 3 it can be seen that: when the ceramic coating is placed in the SO2 gas corrosion test chamber with a gas volume of 0.2 dm 3 , after 48 hours of corrosion, there are no phenomena such as cracking, peeling, and blistering on the coating surface.
[0106] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A ceramic coating, characterized in that, By mass percentage, it includes the following components: High-entropy zirconate 20 - 34%, Al2O3 whiskers 1 - 2%, hexagonal boron nitride 1 - 3%, silicon nitride 1 - 3%, cordierite 2 - 4%, chromium oxide 6 - 8%, wetting dispersant 0.3 - 1%, leveling agent 0.3 - 1%, defoaming agent 0.3 - 1%, thickening agent 0.3 - 1%, composite binder 35 - 50% and water 10 - 20%; The chemical formula of the high-entropy zirconate is A2Zr2O7, where the A site contains at least four elements among La, Sm, Nd, Gd, Eu, Yb, Y, Sc, and the elements in the A site are in equimolar ratio; The composite binder includes an organic binder and an inorganic binder.
2. The ceramic coating according to claim 1, characterized in that, The particle size of the high-entropy zirconate is < 1 μm, and the specific surface area is 30 to 80 m 2 / g; The particle size of the hexagonal boron nitride is 200 - 300 nm; The particle size of the silicon nitride is 600 - 800 nm; The particle size of the cordierite <1 μm; The particle size of the chromium oxide <1 μm.
3. The ceramic coating according to claim 1, characterized in that, The wetting dispersant is an anionic wetting dispersant; The leveling agent is a silicone leveling agent; The defoaming agent is one or more of silicone defoaming agents, polyether silicone defoaming agents and mineral oil-based defoaming agents; The thickening agent is a polyurethane thickening agent and / or a non-ionic thickening agent.
4. The ceramic coating according to claim 1, characterized in that, The organic binder includes one or more of styrene-acrylic emulsion, silicone-acrylic emulsion and pure acrylic emulsion; in the ceramic coating, the mass percentage of the organic binder is 15 - 25%; The inorganic binder includes one or more of potassium silicate water glass, sodium silicate water glass and lithium silicate water glass; in the ceramic coating, the mass percentage of the inorganic binder is 20 - 35%.
5. The preparation method of the ceramic coating according to any one of claims 1 to 4, characterized in that, It includes the following steps: First mix the wetting dispersant, leveling agent, defoaming agent, thickening agent and water to obtain a first system; Second mix the high-entropy zirconate, Al2O3 whiskers, hexagonal boron nitride, silicon nitride, cordierite, chromium oxide and composite binder to obtain a second system; After the first system and the second system are third mixed, grinding is carried out to obtain the ceramic coating.
6. The preparation method according to claim 5, characterized in that, The rotation speed of the first mixing is 2000 - 2500 r / min, and the time is 5 - 15 min; The rotation speed of the second mixing is 600 - 800 r / min, and the time is 10 - 20 min; The rotation speed of the third mixing is 200 - 300 r / min, and the time is 30 - 40 min; The grinding balls for the grinding are zirconia grinding balls, the rotation speed of the grinding is 300 - 500 rpm, and the time is 2 - 3 h.
7. Application of the ceramic coating according to any one of claims 1 - 4 in the field of protection.
8. The method for using the ceramic coating according to any one of claims 1 to 4, characterized in that, It includes the following steps: Perform sandblasting on the substrate to be protected to obtain a treated substrate; Spray the ceramic coating according to any one of claims 1 - 4 on the treated substrate, and successively carry out first curing and second curing to form a protective layer.
9. The method of use according to claim 8, wherein The parameters of the sandblasting treatment include: the particle size of the corundum sand is 24 - 150 mesh, and the pressure is 0.5 - 2 MPa; The pressure of the spraying is 0.4 - 1.5 MPa, the ambient temperature is 15 - 25 °C, and the relative air humidity is 40 - 60%.
10. The usage method according to claim 8, characterized in that, The time of the first curing is 12 - 24 h; The temperature of the second curing is 200~600°C, and the time is 2~6h.
Citation Information
Patent Citations
Gadolinium zirconate-based high-entropy ceramic thermal barrier coating powder as well as preparation method and application thereof
CN115894027A
High-entropy ceramic thermal barrier coating and preparation method thereof
CN116377372A
High-entropy rare earth zirconate ceramic coating with low thermal conductivity and high wear resistance and preparation method of high-entropy rare earth zirconate ceramic coating
CN117535613A
High-entropy cerate water-based paint with high-temperature radiation heat dissipation function and coating of high-entropy cerate water-based paint
CN118126547A
High-entropy rare-earth zirconate ceramic with excellent thermal physical property and high mechanical property and preparation method of high-entropy rare-earth zirconate ceramic
CN118878322A